2022
DOI: 10.1155/2022/9310710
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training Intensity on VO2max in Healthy Adults: An Overview of Systematic Reviews and Meta-Analyses

Abstract: This study aimed to evaluate systematic reviews and meta-analyses that have examined the effect of exercise training on VO2max in healthy individuals at different intensities. Five databases were searched: EBSCOhost, MEDLINE/PubMed, SPORTDiscus, Web of Science, and Google Scholar. Eligibility criteria for selecting reviews included systematic reviews and meta-analyses of healthy adults that examined the effect of lower intensity training (LIT) and/or high intensity training (HIT) on VO2max. Eleven reviews met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…This metric, while improved post intervention, did not reach statistical significance, similar to previously published findings in PD [91]. This may result from an insufficient aerobic training dosage to bring about a cardiovascular training response in the integrated exercise programme [92] or from low study numbers with insufficient power. Disaggregation of VO2 max by sex, Table 3 identified differences, whereby estimated VO2 max was higher than normative data in females, most likely driven by one outlier in the group.…”
Section: Plos Onesupporting
confidence: 74%
“…This metric, while improved post intervention, did not reach statistical significance, similar to previously published findings in PD [91]. This may result from an insufficient aerobic training dosage to bring about a cardiovascular training response in the integrated exercise programme [92] or from low study numbers with insufficient power. Disaggregation of VO2 max by sex, Table 3 identified differences, whereby estimated VO2 max was higher than normative data in females, most likely driven by one outlier in the group.…”
Section: Plos Onesupporting
confidence: 74%
“…Meta-regression and analysis of 28 articles highlighted an increase in VO 2 max with physical activity training, independent of the volume and intensity of exercise sessions [ 60 ]. Crowley et al reported in their systematic review that both high and low intensity training when undertaken frequently increased VO 2 max [ 61 ]. Interestingly, despite adjusting for physical activity levels, Gostelow and Stohr found a significantly lower VO 2 max in individuals born at VLBW [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adults born at VLBW are at a higher risk of hypertension [ 61 ], heart failure [ 62 ], diabetes [ 63 ], and cardiometabolic syndromes [ 61 ]. Interestingly, despite a greater prevalence of cardiovascular risk factors, an association with ischemic heart disease remains inconclusive [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, perubahan struktur dan jumlah arteriol, arteriol dan kapiler, sesuai dengan kebutuhan aliran darah meningkat selama latihan, adalah kompensasi tubuh untuk berolahraga, diikuti dengan peningkatan VO2max. (Crowley et al, 2022). Hasil yang berbeda didapatkan oleh Scribbans et al (2016) yang menunjukkan bahwa besarnya peningkatan penyerapan oksigen maksimal yang diinduksi oleh latihan fisik tidak dipengaruhi oleh intensitas latihan Namun, latihan dengan dosis latihan yang rendah dan intensitas yang tinggi memberikan nilai VO2max yang lebih besar dibandingkan latihan dengan dosis tinggi dan intensitas rendah Keikutsertaan seorang atlet dalam suatu event olahraga tidak terkecuali dengan mendambakan sebuah prestasi di Pesta Olahraga Nasional (PON).…”
Section: Pendahuluanunclassified